UNDERGROUND CRUCIFORM STRUCTURE IN NARYN-KALA: A CHURCH? PRO ET CONTRA - Gadziev, Murtazali Serazutdinovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article discusses the interpretation of a mysterious underground building, situated in the Derbent citadel Naryn-Kala. This monumental structure is a crucifix (Latin cross) in plan, oriented with a long axis along the NNW-SSE line, roofed with pointed arches and a dome. On the plans of the citadel of Derbent in the early-mid-19th century, this underground building is indicated as a cruciform structure with the caption “water reservoir”. In historical, reference literature and documentation it is defined as an underground water reservoir of the 17th – 18th centuries. In 1976, A.A. Kudryavstev first suggested that this building was originally a church of the 5th – 6th centuries. After almost 40 years, his suggestion was recognized as an established fact, however, with no solid ground or any supplementary reasons. At the same time, distortion of facts and forgery were recorded. This unfounded opinion was promoted even by high-ranking government officials. In 1998, G.M. Kurbanov assumed a possible interpretation of this site as a Zoroastrian fire temple. In 2020, V.L. Myts speculated that this is a Christian martyrium. However, architectural and archeological data contradict these interpretations: the land-based, early medieval, or religious nature of the building has not been proved. Comprehensive (architectural, archeological, magnetometric, etc.) study of this site, without large-scale archeological excavations, is needed.
Keywords: Derbent; Christianity; Zoroastrianism; cruciform water reservoir; cross-dome church; fire temple; martyrium